factor X^3+X^2-6X

first factor X

==> x(x^2+x-6)

Now factor the equation (x^2+x-6)

==> x(x+3)(x-2)

If you need to obtain the eqution's roots, then you need to find x values in which the equation equals 0

==> x(x+3)(x+2)=0

==> x = 0, -3, and -2

## Unlock

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

factor X^3+X^2-6X

first factor X

==> x(x^2+x-6)

Now factor the equation (x^2+x-6)

==> x(x+3)(x-2)

If you need to obtain the eqution's roots, then you need to find x values in which the equation equals 0

==> x(x+3)(x+2)=0

==> x = 0, -3, and -2